1994
DOI: 10.1002/mrd.1080370312
|View full text |Cite
|
Sign up to set email alerts
|

Production of motile acrosome‐reacted mouse sperm with nanomolar concentration of calcium ionophore A23187

Abstract: A method to generate a population of motile, acrosome-reacted mouse sperm is described. Sperm retrieved from the cauda epididymis and vas deferens were first capacitated in a 3% bovine serum albumin (BSA) containing medium. Sperm were then resuspended in medium with low BSA content (0.01%) and treated with 30 nM of the calcium ionophore, A23187, which was added as a single dose of 30 nM for 15 min at 37 degrees C; or three sequential 10 nM doses over three 5 min intervals. Approximately 55-60% of the treated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Conversely, sperm exposed to a ten-fold increase in cauda epididymal calcium concentration in mice mutant in TRPV6 (transient receptor potential vanilloid 6) that is a calcium ion selective channel, display increased intracellular calcium and have a markedly reduced motility and fertilization capacity [33]. In addition, sperm induced with 10 µM of the calcium ionophore A23187 will undergo the AR, but will become immotile [34].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, sperm exposed to a ten-fold increase in cauda epididymal calcium concentration in mice mutant in TRPV6 (transient receptor potential vanilloid 6) that is a calcium ion selective channel, display increased intracellular calcium and have a markedly reduced motility and fertilization capacity [33]. In addition, sperm induced with 10 µM of the calcium ionophore A23187 will undergo the AR, but will become immotile [34].…”
Section: Resultsmentioning
confidence: 99%
“…However, excessive intracellular calcium may induce microtubule defects and premature AR39. Such sperm will lose motility50 and the ability to firmly bind to the zona pellucida39 despite being capable of penetrating the egg5152. It is currently unclear whether such an excessive increase in intracellular calcium level occurs in the absence of PRM1, and further studies will be required to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ajduk et al (28), pretreatment of mouse spermatozoa with 20 M Ca 2ϩ ionophore synchronizes pronuclear development of mouse oocytes after ICSI. Because such high concentrations of Ca 2ϩ ionophore immobilizes (''kills'') most spermatozoa (29), the synchronization of pronuclear development Ajduk et al (28) observed is likely because of extensive damage or loss of sperm plasma membranes by influx of excessive Ca 2ϩ . Mouse ICSI using LL-treated spermatozoa resulted in a high percentage of normal live offspring (Table 2).…”
Section: Discussionmentioning
confidence: 99%